Teen Titans : Earth One, Volume 1 - Lemire, Jeff (DC Comics, 2014)
"The Teen Titans never felt like normal kids ... but they had no idea how right they were. Their seemingly idyllic Oregon upbringing hides a secret -- one that will bring killers, shamans, and extraterrestrials down on their heads, and force them into an alliance that could shake the planet to its foundations!"--